2016
DOI: 10.1177/1558944716681974
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Rate of Surgery for Ulnar Collateral Ligament Injury of the Metacarpophalangeal Joint of the Thumb

Abstract: The rate of surgery for acute thumb MP UCL injury varies based on patient characteristics and the individual treating surgeon. Variation might decrease with improved diagnostic techniques and consideration of practice guidelines. Future studies are needed to determine the patients and injuries that will benefit most from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Additionally, our finding of a positive correlation between age and hospitalization rate in DUE fractures was corroborated by a 2010 study from France, which showed hospitalizations due to wrist fractures increased with age every year from 2002 to 2006 [ 9 ]. Age has been shown to be an independent risk factor for both worsened wrist function following certain DUE fractures and the need for surgical repair of DUE fractures [ 10 , 11 ]. Thus, increased aggressive treatment, including hospitalization and surgical repair, of DUE fractures in older adults is important for patient outcomes and is likely contributing to the trends seen in our paper.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our finding of a positive correlation between age and hospitalization rate in DUE fractures was corroborated by a 2010 study from France, which showed hospitalizations due to wrist fractures increased with age every year from 2002 to 2006 [ 9 ]. Age has been shown to be an independent risk factor for both worsened wrist function following certain DUE fractures and the need for surgical repair of DUE fractures [ 10 , 11 ]. Thus, increased aggressive treatment, including hospitalization and surgical repair, of DUE fractures in older adults is important for patient outcomes and is likely contributing to the trends seen in our paper.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study by Stoop et al assessed 383 UCL injuries treated at three different hospitals in a singe American city 11 . In total, 30% of cases were avulsion fractures and 11% of cases were investigated with an MRI scan.…”
Section: Discussionmentioning
confidence: 99%
“…However some factors which were unrelated to patient characteristics were predictive of operative intervention, such as having an MRI and being treated by certain surgeons. It was felt that because the preoperative diagnosis of a Stener lesion has limited reliability and accuracy, the rates of surgery may vary based on surgeon beliefs, preferences and values.They also stated that ”some surgeons believe some non-Stener injuries benefit from operative treatment” 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of associated avulsions, the degree of displacement or rotation are primary factors in deciding initial management. Avulsion fracture displacement >2 mm has been associated with patients needing to undergo surgery (42). In contrast to these findings, Dinowitz et al (38) found poor outcomes when managing UCL avulsion fractures with <2 mm displacement conservatively.…”
Section: Managementmentioning
confidence: 99%